QKD (Quantum Key Distribution) Networks: Enhancing Secure Communication Through Entanglement- Based Protocols (Quantum Frontiers Journal P-ISSN 3117-6070 and E-ISSN 3117-6089, 2025)
As digital communication continues to scale globally, cybersecurity vulnerabilities are becoming increasingly sophisticated. Classical encryption methods—based on mathematical complexity—face obsolescence with the advancement of quantum computing, which can break widely used cryptosystems such as RSA and ECC through algorithms like Shor’s. Quantum Key Distribution (QKD) represents a paradigm shift by leveraging the laws of quantum mechanics, particularly photon entanglement and Heisenberg’s uncertainty principle, to establish secure communication channels. Unlike classical cryptography, which relies on computational security, QKD guarantees information-theoretic security, making interception detectable and ineffective. This research paper evaluates entanglement-based protocols, including E91, BBM92, and emerging satellite-assisted QKD networks. The study includes a comparative performance analysis between classical cryptographic techniques and QKD across speed, security breach probability, latency, and scalability. A real-world case study of China’s Micius Quantum Satellite Network is used to illustrate practical deployment. Findings show that QKD reduces key interception vulnerability to near zero, while classical systems remain susceptible to brute-force and eavesdropping attacks. Data demonstrate that entanglement-based QKD outperforms other quantum protocols in long distance secure communication and offers a scalable foundation for the future quantum internet.